2003
DOI: 10.1159/000074523
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms in Type 1 Diabetic Patients, as Compared to a General Population

Abstract: Objectives: To examine the prevalence of gastrointestinal (GI) symptoms in patients with type 1 diabetes as compared to age- and sex-matched controls. Method: 395 patients with type 1 diabetes, registered at the diabetes outpatient unit at the Sahlgrenska University Hospital, were studied by use of a GI symptom questionnaire. They were randomly selected within 10-year age intervals from 20 to 69 years. Age- and sex-matched controls (n = 242) were sampled from a cohort recruited from the general population. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
(27 reference statements)
1
23
0
1
Order By: Relevance
“…In an Olmstead County community survey, however, no differences in the rates for nausea or vomiting could be detected in either type 1 or type 2 diabetic patients compared to the nondiabetic residents [26]-raising questions regarding the pathogenetic significance of diabetes toward the symptoms. A recent study of nearly 400 type 1 diabetic patients did find a mild increase in upper GI symptoms in the diabetic group compared with nondiabetic subjects, especially symptoms of higher intensity [27]. Symptoms were not predicted by degree of glycemic control nor presence of peripheral neuropathy in these type 1 subjects who have more difficulty with diabetes management and more neuropathic complications than type 2 patients.…”
Section: Discussionmentioning
confidence: 78%
“…In an Olmstead County community survey, however, no differences in the rates for nausea or vomiting could be detected in either type 1 or type 2 diabetic patients compared to the nondiabetic residents [26]-raising questions regarding the pathogenetic significance of diabetes toward the symptoms. A recent study of nearly 400 type 1 diabetic patients did find a mild increase in upper GI symptoms in the diabetic group compared with nondiabetic subjects, especially symptoms of higher intensity [27]. Symptoms were not predicted by degree of glycemic control nor presence of peripheral neuropathy in these type 1 subjects who have more difficulty with diabetes management and more neuropathic complications than type 2 patients.…”
Section: Discussionmentioning
confidence: 78%
“…R ecent studies indicate that the prevalence of gastrointestinal symptoms in patients with type 1 diabetes (DM1) is greater than that observed in the overall population (1)(2)(3). It was also demonstrated that this clinical picture has a negative impact in the quality of life of these patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that investigated the relationship between digestive symptoms and Helicobacter pylori infection (8), glycemic control (1,9), and abnormal autonomic function (5) in diabetes also showed contradictory results. Besides, no direct relationship was demonstrated between diabetic gastroparesis and specific digestive symptoms (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The symptom profile of diabetic gastroenteropathy includes nausea, vomiting, early satiety, constipation, diarrhoea, abdominal pain and bloating. These symptoms may occur alone or in combination 6 . The diverse nature of the symptoms suggests a multifactorial cause for diabetic gastroenteropathy.…”
Section: Introductionmentioning
confidence: 99%